Zur Verbreitung von Informationen in sozialen Netzwerken - eine wirtschaftspolitische Analyse - Schulz, Hannah

Integrierte Entwicklung komplexer Systeme mit modellbasierter Systemspezifikation und -simulation - Roßmann, Jürgen; Schluse, Michael; Rast, Malte; Hoppen, Martin; Dumitrescu, Roman; Bremer, Christian; Hillebrand, Michael; Stern, Oliver; Blümel, Florian; Averdung, Christoph (Wissenschaftsforum Intelligente Technische Systeme (WinTeSys))

Approach for identifying components worthy of protection of Cyber-Physical Systems (CPS) based on a system model - Kliewe, Daniel; Kaiser, Lydia; Dumitrescu, Roman; Gausemeier, Jürgen (Jurnal Teknologi)

Implementing Model-Based Systems Engineering based on Shared Services - Concepts for Industrial Application - Bansmann, Michael; Tschirner, Christian; Dumitrescu, Roman (1st IEEE International Symposium on Systems Engineering (ISSE), Rome, Italy, 2015)

Why Fit Leads to Surprise: An Extension of Cognitive Fit Theory to Creative Problems - John, Thomas; Kundisch, Dennis (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth, USA)
Cognitive fit theory (CFT) provides guidance for how best to represent information that is relevant for solving a given problem. CFT is widely established in information systems research and its validity has been demonstrated in a great variety of contexts. However, of the two major types of problems that exist (i.e., routine and creative problems) prior CFT research has addressed only one: routine problems. Creative problems, despite their importance, have been left unaddressed. Therefore, based on the visual sketching model of problem solving, we propose an extension of CFT and thereby demonstrate that cognitive fit can promote problem solving performance also for creative problems. In doing so, we extend the boundary of CFT and add to creativity research a previously unknown cognitive mechanism for promoting creative performance: cognitive fit. Moreover, we contribute to general problem solving research by bridging the gap between problem solving in creativity and information systems research.

Feature Model Approach For Managing Variability of Dynamic Behavior Models in Mechatronic Systems - Abrishamchian, Farisoroosh; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2015 International Mechanical Engineering Congress & Exposition)

Decentralized Controller Reconﬁguration Strategies for Hybrid System Dynamics based on Product-Intelligence - Bertelsmeier, Fabian; Trächtler, Ansgar (20th IEEE International Conference on Emerging Technologies and Factory Automation)

Flexible Operation Workflow of a Driving Simulation Center for ADAS Development - Abdelgawad, Kareem; Hassan, Bassem; Kohlstedt, Andreas; Stöcklein, Jörg; Berssenbrügge, Jan; Grafe, Michael; Gausemeier, Sandra; Jäker, Karl-Peter; Trächtler, Ansgar (New Developments in Driving Simulation Design and Experiments)

ARTiST - An Augmented Reality Testbed for Intelligent Technical Systems - Hassan, Bassem; Stöcklein, Jörg; Berssenbrügge, Jan (Virtual, Augmented and Mixed Reality VAMR 2015 Held as Part of HCI International 2015)

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Proceedings of the ASME 2015 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)